107k views
1 vote
Given: 2e - 1 = 2d + 15,
c=e-d
Prove: c = 8

Given: 2e - 1 = 2d + 15, c=e-d Prove: c = 8-example-1

2 Answers

3 votes


2e - 2d = 15 + 1 \\ 2e - 2d = 16 \\ 2(e - d) = 16 \\ (2(e - d))/(2) = (16)/(2) \\ e - d = 8

FROM THE EQUATION WE FIND THAT e-d =8

AND THERE IS A GIVEN STATEMENT THAT c=e-d

THEREFORE c=8 SINCE BOTH C AND 8 ARE EQUAL TO e-d

GOODLUCK

User Msahin
by
6.1k points
3 votes

Answer:


e =(2d +16)/(2)


c = e-d\\c= d + 8 -d\\c = 8

User Nilaksha Perera
by
5.6k points